Is nuclear power more competitive producing electricity or hydrogen?. (8th November 2006) - Rothwell, Geoffrey; Williams, Kent
Steam methane reforming is the world's dominant hydrogen production technology, using natural gas as both feedstock and fuel, but producing more than 9 kg of CO2 for each kilogram of H2 . Natural gas prices between $6 and $8/GJ yield an average hydrogen production cost between $12 and $15/GJ, excluding the cost of CO2 . High-temperature gas reactors, e.g. the modular helium reactor, can be configured to produce hydrogen using thermochemical processes with a projected average cost of $15/GJ. Also, spent fuel from modular helium reactors is well suited for very long-term repository storage. However, natural gas prices of $8/GJ make electricity generation from modular helium reactors extremely competitive with respect to combined-cycle gas turbines. Therefore, the modular helium reactor is likely to be more profitable in electricity markets than in hydrogen markets under carbon restriction regimes.